2011
DOI: 10.4314/ajesms.v8i1.69109
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate pre-service chemistry teachers’ conceptions about inorganic qualitative analysis

Abstract: The research was a baseline study to determine the perceptions and alternative concepts that pre-service teachers' have which hinder them from making correct inferences during practical inorganic chemistry experiments. A two-tier qualitative analysis diagnostic instrument (QADI) was developed and used to diagnose and treat the participants' alternative concepts in inorganic chemistry qualitative analysis. The diagnostic instrument was administered to 78 pre-service teachers in the University of Education, Winn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Studies have shown that learners have little comprehension of the idea of hybridization because there is evidence that many cannot distinguish between atomic and hybrid orbitals (Hanson et al, 2012). The failure of students to distinguish between pure atomic and hybrid orbitals indicates a foundational difficulty in the prerequisite concepts (Hanson et al, 2012). Other weaknesses in hybridization include the inability to distinguish between single, double, and triple bonds in unsaturated and saturated hydrocarbon.…”
Section: Effect Of Computer Animation Instructional Package On …mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that learners have little comprehension of the idea of hybridization because there is evidence that many cannot distinguish between atomic and hybrid orbitals (Hanson et al, 2012). The failure of students to distinguish between pure atomic and hybrid orbitals indicates a foundational difficulty in the prerequisite concepts (Hanson et al, 2012). Other weaknesses in hybridization include the inability to distinguish between single, double, and triple bonds in unsaturated and saturated hydrocarbon.…”
Section: Effect Of Computer Animation Instructional Package On …mentioning
confidence: 99%
“…Additionally, they are anticipated to ascertain the nature of the hybridization of the core atoms in molecules with various shapes. The curriculum allows the learner to learn the introductory aspects of hybridization, which is required for understanding hybridization, and related topics necessary for success in many chemistry courses in post-secondary education (Hanson et al, 2012). Given the relevance of hybridization, efforts should be directed toward students' poor performance (Koomson et al, 2020).…”
Section: Effect Of Computer Animation Instructional Package On …mentioning
confidence: 99%
“…Researchers found that prospective teachers hold onto alternative conceptions about atomic orbitals and hybridization [24]. Students have shown difficulties in learning about hybridization where they assumed that shells and orbitals are the same, could not differentiate between atomic orbitals and molecular orbitals, and confused bonding electrons in hybrid orbitals with s, p, or d orbitals [25].…”
Section: Iss2art4mentioning
confidence: 99%
“…Some of these difficulties include teaching techniques and approaches (Sahin et al, 2016;Udogu et al, 2007) used by the teachers, as well as the teachers' content knowledge and assessment methods (Abell, 2007;Sakim, 2004) used by the teachers among others. These difficulties have also been found to have an impact on students' academic achievements (Hanson et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…However, in teaching and learning, the topic hybridization has been identified as one of the most abstract and difficult concept for classroom instruction (Abukari et al, 2022;Calis, 2018;Jian, 2014;Salah & Dumon, 2011). Research conducted have revealed that students have difficulties in learning the concept of hybridization by Abukari et al (2022), Calis (2018), Hanson et al, (2012), Jian (2014), Koomson et al, (2020), Nakiboglu (2003), and Salah and Dumon (2011). Some of the difficulties students experience in learning hybridization has been attributed to gaps in teacher knowledge in teacher training (Rollnick & Mavhunga, 2014).…”
Section: Introductionmentioning
confidence: 99%